2014
DOI: 10.14740/wjon799w
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Laser Conization for Cervical Intraepithelial Neoplasia 2-3 and Microinvasive Cervical Cancer

Abstract: BackgroundCurrently, there is no standardized follow-up protocol for patients who undergo laser conization. Therefore, we retrospectively investigated the clinical outcomes of laser conization in patients with high-grade cervical intraepithelial neoplasia 2-3 (CIN 2-3) and microinvasive squamous cell carcinoma and assessed the risks of residual and recurrent lesions of the cervix uteri.MethodsThe medical and pathological records of 91 patients with CIN 2, 580 with CIN 3 and 73 with microinvasive cervical cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
3
3
0
1
Order By: Relevance
“…18 This was probably because all excisions were performed by the same experienced operator, a condition that is reported to be associated with lower rates of positive margins. 19 The global rate of positivity at follow-up (7.7%) was comparable with that found in previous studies for CO 2 laser excisions, which was 3.4% to 16.7% 1,[20][21][22][23] ; more specifically, our rate of positivity at follow-up in the case of positive margin was 20.5%, similar to that found by Arbyn et al 1 (14.1%; 95% CI, 3.0%-29.5%) 1 and the rate of positivity at follow-up in the case of close endocervical margin was slightly superior (8.3% versus 3.7%; 95% CI, 2.5%-5.1%), but still not significantly different from that of women with negative margins in our population (8.3% versus 7.0%, P ¼ .89). This small discrepancy must be interpreted with caution, because it could reflect the intrinsic characteristics of our population, independent from the histologic characterization of surgical margins.…”
Section: Discussionsupporting
confidence: 87%
“…18 This was probably because all excisions were performed by the same experienced operator, a condition that is reported to be associated with lower rates of positive margins. 19 The global rate of positivity at follow-up (7.7%) was comparable with that found in previous studies for CO 2 laser excisions, which was 3.4% to 16.7% 1,[20][21][22][23] ; more specifically, our rate of positivity at follow-up in the case of positive margin was 20.5%, similar to that found by Arbyn et al 1 (14.1%; 95% CI, 3.0%-29.5%) 1 and the rate of positivity at follow-up in the case of close endocervical margin was slightly superior (8.3% versus 3.7%; 95% CI, 2.5%-5.1%), but still not significantly different from that of women with negative margins in our population (8.3% versus 7.0%, P ¼ .89). This small discrepancy must be interpreted with caution, because it could reflect the intrinsic characteristics of our population, independent from the histologic characterization of surgical margins.…”
Section: Discussionsupporting
confidence: 87%
“…This study demonstrated 87.8% of cure rate in primary resection which was in the range of 73% to 99% reported from previous studies [5][6][7][8]11]. On the other hand, our 12.2% failure rate was much lower than 26% reported by Serati et al which used CKC [5].…”
Section: Discussionsupporting
confidence: 47%
“…Various rates of cure or failure from each study may depend on many factors aside from the surgical procedure itself, e.g., personal features of the patients, practice of surgeon including the skill and aggressive surgical approach, duration of follow-up, timing to define failure, immediate outcomes of surgery including surgical margin, etc. [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations